The Influence of Legal Environment upon Accounting in Libya - EL-SHARIF, YOUNIS (Dirasat in Economics and Business, 1981)
During the last twenty years accounting in Libya as in many other economies had an important function in the Libyan economy. The accounting function as defined by one author includes measurement and communication of economic data. l Also the importance of this function was emphasized by one of the former presidents of the American Institute of Certified Public Accountants as follows: One thing that holds the economy together under all the pressures, and in the midst of this swift evolutionary passage through time, is our system offinancial reporting . . without adequate information about the results of business operations no one could make intelligent decisions, and our economy wouldfall apart? Investors, creditors, management, as well as state agencies need much more reliable information in order to make important decisions related to the economic development of Libya. Therefore, the Libyan accounting profession must be developed to fulfill these new demands Although accounting development in general have been influenced by the social, economic and legal environment, the modern accounting profession in Libya is relatively new. Until few years ago there was no considerable action to have any professional accounting organization as it is known in other developed countries. Law No. 1 16 of 1973 was the first complete regulation to be enacted in order to organize the accounting profession in Libya. However, the formation of the organization of Libyan Accountants and Auditors was not completed until 1976. Not much work has been completed by this organization to date.